Evaluation of Keycloak as an identity server versus commercial solutions in multiplatform organizational environments - Vereau Jacobo, Edwin Wilfredo (LACCEI, 2025)
This systematic review analyzed the effectiveness of Keycloak as a centralized identity server compared to commercial solutions in organizations with multiple independent systems, evaluating benefits, challenges, and practical implementations in diverse organizational contexts. Information searches were conducted in Scopus and IEEE Xplorer databases for articles published between 2020-2025, applying PRISMA criteria and PICOC analysis to select 40 studies that addressed Keycloak implementations and comparisons with commercial solutions. Narrative synthesis organized results by specific research questions related to organizational challenges, implementation, comparison, efficiency, and application contexts. The results demonstrate that Keycloak achieves significant reductions of 40-62% in identity management time, 68% in compromised credential incidents, and 60-80% in total cost of ownership compared to commercial solutions. Its modular architecture supports standard protocols (SAML 2.0, OpenID Connect, OAuth 2.0) facilitating integration with heterogeneous systems, with successful implementations from 100 to 50,000+ users in government, educational, healthcare, and enterprise sectors, maintaining response times of 200-300ms under high loads. It is concluded that Keycloak constitutes a viable and economical alternative to commercial solutions, offering equivalent functional capabilities with greater flexibility and customization, requiring careful migration planning and specialized technical expertise for successful implementations.